Screening Non-Improved Zimbabwean Sorghum Land Races for Resistance to Witch Weed (Bangladesh Agronomy Journal, 2017)
Sorghum is an important cereal for food security in semi-arid regions of the world (Mukarumbwa and Mushunje 2010). Semi-arid regions are characterized by frequent droughts leading to crop failure. In addition to drought, sorghum production in the smallholder farming sector in Sub-Saharan Africa can be undermined by the parasitic witch weed Striga asiatica (L.) Kuntze (Stroud, 1993). S. asiatica parasitism can cause cereal yields to drop by as much as 60% hence it poses a threat to food security (Mabasa, 1993). The aim of this study is to screen sorghum landraces for S. asiatica resistance and test the escape hypothesis through a controlled in a pot experiment. A pot experiment was established on 1 March 2013 at the Henderson Research Station in Zimbabwe. It is situated in agro-ecological region II of Zimbabwe. The annual average rainfall is 864 mm. Mean annual temperature is 21 oC (Mujere and Mazvimavi, 2012). The dominant soil type is red clay loam belonging to the fersiallitic group (Wulff et al. 2002). Four sorghum (Sorghum bicolor) landraces consisting of two early maturing and two late maturing varieties were obtained from the National Genebank in Harare for this experiment. The early maturing landraces were Tsveta and Nhongoro while the late maturing landraces were Musoswe and Khaki. The biological characteristics of these landraces including days to 50% flowering is shown in Table 1.Bangladesh Agron. J. 2017, 20(1): 106-108